Qualidade de vida e Síndrome de Burnout entre médicos intensivistas em Salvador, Bahia, Brasil - Barros, Dalton de Souza (2012)
Studies have demonstrated the occurrence of mental health problems in health professionals, including those working in intensive care. However there are few studies evaluating both mental health and quality of life of these professionals. We aimed evaluate the correlation between burnout syndrome and quality of life of ICU attending physicians in Salvador. It was conducted a cross-sectional study in a population of 333 adult ICU attending physicians in Salvador, through a self-administered questionnaire, consisting the Maslach Burnout Inventory (MBI) to measure the burnout syndrome, beyond the realms of quality of life (QOL) measured by the WHOQOL-Bref. The Pearson correlation coefficients (r) between burnout and emotional exhaustion of the domains of QOL ranged from - 0.41 to -0.58, with the highest correlation occurred with the dimension of the psychological domain. Already on the depersonalization dimension of burnout, the correlation values were - 0.17 to - 0.33. And the size ineffectiveness, the correlation ranged from 0.16 to 0.31. Physicians with high levels in any of the three dimensions of burnout syndrome had lower scores of quality of life in four domains (WHOQOL-Bref). The results indicate a correlation between Burnout and the domains of WHOQOL-Bref.